Application of temporarily functional antibiotic-containing bone cement prosthesis in revision hip arthroplasty - Liu, Ke (Springer Paris, 2012)
PURPOSE: To investigate the clinical outcome of two-stage revision total hip arthroplasty for infected hip arthroplasty using antibiotic-impregnated cement prosthesis. MATERIALS AND METHODS: Forty-one patients, who suffered from an infection after hip replacement or internal fixation of femoral neck and trochanteric fractures, were treated with a two-stage revision hip arthroplasty and followed up for an average of 37 months. All the patients were implanted with antibiotic-impregnated cement prosthesis as one-stage treatment and were then managed with two-stage revision hip arthroplasty after 12–24 weeks. During the follow-up, Merle d’Aubigné hip score and Harris score were employed for assessment of hip function, and infection recurrence was observed. RESULTS: According to Merle d’Aubigné hip score, 16 patients (39.2 %) were excellent, 19 (46.3 %) were good, 6 (14.6 %) were moderate, and no bad result and the average score was 15.42. Mean Harris score of preoperation, interval period, and postoperation was 46.7, 66.5, and 92.3, respectively. There was no infection recurrence. CONCLUSION: Two-stage revision total hip arthroplasty for infected hip arthroplasty using antibiotic-impregnated cement prosthesis has a satisfying clinical outcome.